In the House of the Serpent Handler : A Story of Faith and Fleeting Fame in the Age of Social Media - Waselkov, Gregory A. (Book collections on Project MUSE., 2019)
"Waselkov's collection of essays on Native American log cabins in the southeast stems from a session presented for the Southeastern Archaeological Conference (SEAC) in Athens, Georgia. The essays range in focus from Cherokee domestic space to Seminole architecture to the influence of enslaved Africans in the region"--